Training specialists for transport industry: problems and prospects - Ivan K. Andronchev; Lyudmila F. Krasinskaya (Высшее образование в России)
The article analyzes some problems of transport specialist training and identifies prioritytasks for a transport university complex. These tasks are as follows: providing of the continuity of multi-level training, providing of the state-of-the-art equipment for education, vocational training and scientific research, developing of the new forms of cooperation with transport enterprises, improving of the teachers’ continuing training system.